1985
DOI: 10.1128/iai.48.3.671-675.1985
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polypeptide composition and antigenic components of Rickettsia tsutsugamushi by polyacrylamide gel electrophoresis and immunoblotting

Abstract: Polyacrylamide gel electrophoresis of lysates of purified Rickettsia tsutsugamushi revealed as many as 30 polypeptide bands, including major bands corresponding to molecular sizes of 70, 60, 54 to 56, and 46 to 47 kilodaltons. Compared with the polypeptide composition of the rickettsiae of Gifliam, Karp, and Kato strains and a newly isolated Shimokoshi strain, the major polypeptide in the Kato strain (54-56K) and in the Karp strain (46-47K) migrated a little faster and slower, respectively, than the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
103
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 8 publications
(10 reference statements)
10
103
2
Order By: Relevance
“…However, other strain types were found in Thailand [4], and it was also reported that Shimokoshi [5], Kawasaki [6], and Kuroki [7] strains, which were isolated from patients in Japan, were antigenically distinguished from the prototype strains of Gilliam, Karp and Kato. This antigenic variation depends largely on the diversities of the immunodominant 56-kDa type-speci¢c antigen located on the surface of this microorganism [8], and typing of newly isolated strains can be carried out using immuno£uorescent (IF) testing using strain-or type-speci¢c hyperimmune sera or monoclonal antibodies which recognize 56-kDa antigen, or by restriction fragment length polymorphism (RFLP) of 56-kDa protein genes ampli¢ed by polymerase chain reaction (PCR). Many newly isolated strains from patients and natural hosts in Japan and in Taiwan were tested using IF tests with monoclonal antibodies and RFLP analyses, and the isolates were classi¢ed not only into types but also into further subtypes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, other strain types were found in Thailand [4], and it was also reported that Shimokoshi [5], Kawasaki [6], and Kuroki [7] strains, which were isolated from patients in Japan, were antigenically distinguished from the prototype strains of Gilliam, Karp and Kato. This antigenic variation depends largely on the diversities of the immunodominant 56-kDa type-speci¢c antigen located on the surface of this microorganism [8], and typing of newly isolated strains can be carried out using immuno£uorescent (IF) testing using strain-or type-speci¢c hyperimmune sera or monoclonal antibodies which recognize 56-kDa antigen, or by restriction fragment length polymorphism (RFLP) of 56-kDa protein genes ampli¢ed by polymerase chain reaction (PCR). Many newly isolated strains from patients and natural hosts in Japan and in Taiwan were tested using IF tests with monoclonal antibodies and RFLP analyses, and the isolates were classi¢ed not only into types but also into further subtypes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, since in our own (16) and other studies (4, 11) on R. tsutsugamushi polyclonal antisera raised in animals were used, it was difficult to make solve the problems regarding antigenic identity at the strain or type level. Monoclonal strain-specific antibodies to prototype strains of R. tsutsugamushi produced by the hybridoma technique (20) appear to be useful for both serotyping (4,11,16) and antigenic analysis (3,6,7,15) of the rickettsiae. The present study deals with the production of murine monoclonal strain-specific antibodies against Gilliam, Karp, and Kato strains of R. tsutsugamushi and the characterization of the antibodies prepared.…”
mentioning
confidence: 99%
“…SDS-PAGE. Sodium dodecyl sulfate-polyacrylamide slab gel electrophoresis (SDS-PAGE) was performed by a modification of the Laemmli method (10) as described previously (15). The stacking gel contained 4.5% acrylamide, 0.12% bisacrylamide, and 0.1 % SDS in 0.125 M tris hydrochloride buffer (pH 6.8), and the separation gel contained 10% polyacrylamide, 0.26% bisacrylamide, and 0.1 % SDS in 0.375 M tris hydrochloride buffer (pH 8.8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 56 kDa protein is the immunodominant antigen detected in the sera of scrub typhus patients (15,21). DNA sequence analysis of 56 kDa immunodominant protein genes from six O. tsutsugamushi strains revealed that the sequences may be divided into four conserved and four variable domains (8,14).…”
mentioning
confidence: 99%